European Charter of local self - government - is a basis of effectiveness of a decision maning in the local authorities and administrative agencies - Боярська, Зоя Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The principal directions of effectiveness improvement of executive decision making by the local anthoritiesof Ukraine are examined in this article.